The Alternative Sigma Factor RpoE2 Is Involved in the Stress Response to Hypochlorite and in vivo Survival of Haemophilus influenzae - Nasreen, Marufa; Fletcher, Aidan; Hosmer, Jennifer; Zhong, Qifeng; Essilfie, Ama-Tawiah; McEwan, Alastair G.; Kappler, Ulrike (Frontiers in Microbiology, 2021)
Extracytoplasmic function (ECF) sigma factors underpin the ability of bacteria to adapt to changing environmental conditions, a process that is particularly relevant in human pathogens that inhabit niches where human immune cells contribute to high levels of extracellular stress. Here we have characterized the previously unstudied RpoE2 ECF sigma factor from the human respiratory pathogen Haemophilus influenzae (Hi) and its role in hypochlorite induced stress. Exposure of Hi to oxidative stress (HOCl, H2O2) increased rpoE2 gene expression, and activity of RpoE2 was controlled by a cytoplasmic, 67aa antisigma factor, HrsE. RpoE2 regulated expression of the periplasmic MsrAB peptide methionine sulfoxide reductase that in Hi is required for HOCl resistance, thus linking RpoE2 to HOCl stress. Interestingly, a HirpoE2 strain had wild-type levels of resistance to oxidative stress in vitro, but HirpoE2 survival was reduced 26-fold in a mouse model of lung infection, demonstrating the relevance of this sigma factor for Hi pathogenesis. The Hi RpoE2 system has some similarity to ECF sigma factors described in Streptomyces and Neisseria sp. that also control expression of msr genes. However, HiRpoE2 regulation extended to genes encoding other periplasmic damage repair proteins, an operon containing a DoxX-like protein and also included selected OxyR-controlled genes. Based on our results we propose that the highly conserved Hi RpoE2 sigma factor is a key regulator of Hi responses to oxidative damage in the cell envelope region that controls a variety of target genes required for survival in the host.